Internet Protocol Television At The Access Networks Of The New Generation - Szymeczek, Andrzej (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2018)
The aim of the project is to make the network where IPTV service is functional and after then to test the facilities and specifications of this network. The resoults were gain by the simulator program GNS3 by using real devices.
Keywords: IPTV; Bandwidth; RTP; Multicast; IGMP; GNS3